Islamic education in Malaysia: a critical analysis of its evolution and relevance - Mughal, Muhammad Junaid; Ibrahim, Haslina (University of Punjab Pakistan, 2021)
The arrival of Islam in Malay world inspired the locals to acquire the knowledge of Islam and provide their children Islamic education. For that purpose, hut type institutes were built which have become the major source of Islamic education. This system was known as pondok, went through several phases of reformation and transformation. This paper aims to analyze the development and evolution of Islamic education and its relevance in terms of its implications, focusing on pondok system in Malaysia. To carry out this task, explorative study design was adopted and historical background of pondok and its development were analysed. In addition, a comparative method of analysis was followed to determine the nature of evolution and relevance of Islamic education in Malaysia. The study found that due to the dynamic role of Islamic educational system in the development of society equipped with Islamic values, it remained an essential part of Malay culture, until today. This study also analyzes that how far the Islamic philosophy of education was implemented in religious institutes which encourages the complete development of a person, be it physical, intellectual or spiritual. This paper concludes that graduates of Islamic institutes have significant contribution in the development of society, though, existing system requires further improvements. Hence, there is a need to implement a comprehensive and holistic Islamic educational system which should be based on Islamic philosophical foundation established on Islamic worldview.